2006
DOI: 10.1242/jcs.02881
|View full text |Cite
|
Sign up to set email alerts
|

Caldesmon is an integral component of podosomes in smooth muscle cells

Abstract: Podosomes are highly dynamic actin-based structures commonly found in motile and invasive cells such as macrophages, osteoclasts and vascular smooth muscle cells. Here, we have investigated the role of caldesmon, an actinbinding protein, in the formation of podosomes in aortic smooth muscle A7r5 cells induced by the phorbol ester PDBu. We found that endogenous low molecular weight caldesmon (l-caldesmon), which was normally localised to actin-stress fibres and membrane ruffles, was recruited to the actin cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 81 publications
6
60
1
Order By: Relevance
“…Recent findings have implicated the involvement of podosomes in the invasion of vascular smooth muscle cells in proliferative vascular diseases such as atherosclerosis and restenosis [8]. A7r5 vascular smooth muscle cells have been studied extensively as a model system for investigating the mechanisms of podosome formation by several laboratories [3,4,9,10,11]. Conventional PKC has been found to mediate phorbol dibutyrate (PDBu)-stimulated podosome formation in A7r5 vascular smooth muscle cells [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have implicated the involvement of podosomes in the invasion of vascular smooth muscle cells in proliferative vascular diseases such as atherosclerosis and restenosis [8]. A7r5 vascular smooth muscle cells have been studied extensively as a model system for investigating the mechanisms of podosome formation by several laboratories [3,4,9,10,11]. Conventional PKC has been found to mediate phorbol dibutyrate (PDBu)-stimulated podosome formation in A7r5 vascular smooth muscle cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Erk-dependent phosphorylation of caldesmon has been shown to reverse the ability of the actin-binding carboxyl-terminal fragment of caldesmon to stabilize actin filaments against actin-severing proteins [23]. Recently, Eves et al [10] showed that overexpression of caldesmon suppressed PDBu-stimulated podosome formation, whereas siRNA knock-down of caldesmon expression facilitated PDBu-stimulated podosome formation in A7r5 cells. However, their study did not address the role of Erk-dependent caldesmon phosphorylation in the regulation of podosome formation and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…183,184 In A7r5 cells podosomes are formed upon stimulation with phorbol dibutyrate (PDBu), which activates PKC. Interestingly, l-CaD is present in such podosomes 185 and is phosphorylated at ERK sites. 186 By overexpressing a phosphorylation-deficient CaD-GFP mutant it was found that, although both the size and the lifetime of the podosomes are modulated by ERK-mediated CaD phosphorylation, the modes of ERK and CaD in their modulation of the formation and dynamics of podosomes are different.…”
Section: Phosphorylation As a Regulatory Mechanismmentioning
confidence: 99%
“…155,156,171,185,[188][189][190][191][192] These interesting yet confusing results may have stemmed from (i) the difference of cell types used, (ii) different stages of cells and (iii) different levels of over-expression. Nevertheless, several observations are particularly noteworthy.…”
Section: Nonmuscle Cad and Its Roles During Cell Proliferation And MImentioning
confidence: 99%
“…Caldesmon (CaD) 3 is one such actin "side binder" that exists in nearly all vertebrate cells. Although the muscle-specific isoform of CaD plays a regulatory role in smooth muscle contractility (3), nonmuscle CaD is more broadly implicated in cell motility (4), including processes such as cell migration (5), focal adhesion assembly (6), podosome dynamics (7), and neointimal formation (8). Recently, CaD was also suggested to control a key structural transition occurring during actin polymerization, known as "maturation" (9,10).…”
mentioning
confidence: 99%